Analisis Nilai Pendidikan Moral Cerpen “Istriku” Karya Etik, ST (Kajian Psikoanalisis Sigmund Freud) - Anjani, Nasywa Maudyna; Sihole, Irene Gabriella; Kurniawan, Eva Dwi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
Based on Sigmund Freud's psychoanalytic theory, the